Pengaruh Sikap Wajib Pajak, Pengetahuan Pajak Dan Sosialisasi Pajak Terhadap Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Jember - Wibisono, Nurharibnu (Universitas Merdeka Madiun, 2019)
The purpose of the study was to determine the effect of taxpayer attitudes, knowledge, tax socialization of taxpayer compliance in the Jember Primary Tax Service Office. This type of research is associative research. Data collection techniques using questionnaires, interviews and observations. The analysis technique uses multiple linear regression. The results obtained show that (1) there is an influence of the attitude of the taxpayer on taxpayer compliance in the KPP Pratama Jember.(2) there is the influence of tax knowledge on taxpayer compliance in KPP Pratama Jember. (3) there is an effect of tax socialization on taxpayer compliance at KPP Pratama Jember. (4) there is an influence of the attitude of the taxpayer, tax knowledge and tax socialization of taxpayer compliance in KPP Pratama Jember.Â Keywords: taxpayer attitudes, tax knowledge, tax socialization, taxpayer compliance